2008
DOI: 10.1111/j.0906-7590.2008.05487.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal heterogeneity of macrophyte communities in thirty small, temporary ponds over a period of ten years

Abstract: Citation: Jeffries, Mike (2008) The spatial and temporal heterogeneity of macrophyte communities in thirty small, temporary ponds over a period of ten years. Ecography, 31 (6 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
(58 reference statements)
1
47
0
Order By: Relevance
“…So, the plants provide a characterisation of the local habitat within each pond, reflecting a range of wider environmental influences. (for full details of the plant communities see Jeffries, 2008). The plant communities were used in this study as categorical predictor variables in the models of animal metacommunities (Table 1).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the plants provide a characterisation of the local habitat within each pond, reflecting a range of wider environmental influences. (for full details of the plant communities see Jeffries, 2008). The plant communities were used in this study as categorical predictor variables in the models of animal metacommunities (Table 1).…”
Section: Samplingmentioning
confidence: 99%
“…Other possible matrices were tested and did not give markedly different results. The predictor variables were the length of previous year's summer dry phase, length of previous winter flooding, length of spring dry phase, distance of individual ponds measured as x and y co-ordinates across the array of ponds and plant communities, the latter a factorial variable using the eight plant metacommunities identified by Jeffries (2008) as individual factors. Previous studies of the Hauxley ponds showed that hydrology and plant communities were effective predictor variables in models of species' incidence (Jeffries 2005) and the initial RDA (Figure 2a) confirmed their likely value as predictors of metacommunities.…”
Section: Analysesmentioning
confidence: 99%
“…This in itself represents only a fraction of the overall biological diversity present within ponds. Aquatic macrophytes Jeffries, 2008;Hassall et al, 2012), algae (Asencio, 2014), and Zooplankton (Rundle et al, 2002;Drenner et al, 2009) are also very well represented within ponds and all six species of native UK amphibians (including the protected Great Crested Newt (Triturus cristatus) and the Natterjack Toad (Epidalea calamita)) utilise ponds (Boothby, 1997b;O'Brien, 2014;Peterman et al, 2014). In addition, the following section outlines the ecological importance of ponds to freshwater biodiversity.…”
Section: Macroinvertebrate Biodiversity Within Pond Habitatsmentioning
confidence: 99%
“…Indeed, a number of studies have demonstrated that floral and faunal biodiversity and heterogeneity of invertebrate communities varies over time as well as space (Angélibert et al, 2004;Florencio et al, 2011;Jeffries, 2011;Hassall et al, 2012). Ecological patterns which are difficult to explain based on a single season or 1 year surveys may appear to be heavily influenced by stochastic processes but the patterns may instead be quite deterministic (e.g., historic effects) when examined over a longer temporal scale (Jeffries, 2008;Jeffries, 2011). Addressing the biodiversity of ponds habitats at a range of spatial and temporal scales is vital to increase the knowledge base of pond ecosystems and inform conservation and management practices at the correct spatial scale.…”
Section: Scalementioning
confidence: 99%
“…Macrophyte communities are good surrogates for a wide range of local environmental conditions e.g. physicochemical factors such as pH, nutrients and overall trophic status (Jeffries, 1991a;Costil and Clement, 1996;Nicolet et al, 2004;Della Bella et al, 2008) and variations in habitat type due to local hydrology (Jeffries, 2008) or management (Jeffries, 1991a;Gee et al, 1997). Macrophytes are an important influence on snail communities, providing both physical habitat in which to live and varied surfaces from which snails can graze the periphyton.…”
Section: Introductionmentioning
confidence: 99%